2010
DOI: 10.1029/2008rg000280
|View full text |Cite
|
Sign up to set email alerts
|

Sources and properties of Amazonian aerosol particles

Abstract: [1] This review provides a comprehensive account of what is known presently about Amazonian aerosol particles and concludes by formulating outlook and priorities for further research. The review is organized to follow the life cycle of Amazonian aerosol particles. It begins with a discussion of the primary and secondary sources relevant to the Amazonian particle burden, followed by a presentation of the particle properties that characterize the mixed populations present over the Amazon Basin at different times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
451
1
24

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 354 publications
(492 citation statements)
references
References 253 publications
16
451
1
24
Order By: Relevance
“…Background air, meaning the Amazon basin in the nominal absence of the pollution plume of Manaus, had significant variability associated with it, especially with respect to effective photochemical age. Background variability arose from variations of in-basin emissions and transformations integrated across several days of meteorology as well as, at times, from significant out-of-basin influences and variability tied to transport from the Atlantic Ocean and Africa (28,29). Even so, the effect of the plume, when present, dominated over this background variability for the measured quantities of the present study.…”
Section: Significancementioning
confidence: 76%
“…Background air, meaning the Amazon basin in the nominal absence of the pollution plume of Manaus, had significant variability associated with it, especially with respect to effective photochemical age. Background variability arose from variations of in-basin emissions and transformations integrated across several days of meteorology as well as, at times, from significant out-of-basin influences and variability tied to transport from the Atlantic Ocean and Africa (28,29). Even so, the effect of the plume, when present, dominated over this background variability for the measured quantities of the present study.…”
Section: Significancementioning
confidence: 76%
“…During the dry season, the lower atmosphere is polluted by high aerosol concentrations caused by both biomass burning and prolonged aerosol suspension associated with reduced precipitation Martin et al, 2010). During the wet season, the atmosphere is mostly clean and convective, and the landscape is referred to as the Green Ocean (Roberts et al, 2001;Williams et al, 2002;Andreae et al, 2004) because the convection there resembles storms over blue oceans, where the warm phase in clouds generally produces rain.…”
Section: The Amazon Forest Climatementioning
confidence: 99%
“…Much of this organic material is thought to be of biogenic origin, especially in heavily vegetated areas such as the southeastern United States (6) and the Amazon basin (7). Recent analyses have shown that conversion of biogenic volatile organic compounds (VOCs) to aerosol material can be promoted by anthropogenic pollution (6,8), and chamber studies have revealed a number of biogenic aerosol formation mechanisms in both polluted and clean environments.…”
mentioning
confidence: 99%